Analisis Penguasaan Keterampilan Teknik Dasar Sepakbola Pada Pemain Usia 13-15 Tahun Club Seroja Tanjung Jabung Timur - Azwar, Azwar; Saputra, Adhe; Decheline, Grafitte (Dharmas Journal of Sport, 2026)
Based on the researcher's monitoring based on the coach's statement that the development of the Seroja Tanjung Jabung Timur football game, especially for the 13 to 15 year olds in each match event, experienced many failures, including the failures suspected to be basic technical errors such as inaccurate passing, controlling the ball that often comes loose, shooting inaccurately on target and the ball coming loose from dribbling the ball. All of this is suspected to be caused by the level of poor technical condition ability. The purpose of this study is to determine the mastery of basic football technical skills in players aged 13-15 years of the Seroja Tanjung Jabung Timur Club. This study uses a descriptive research design with a quantitative approach. The sample in this study uses total sampling because the population of the Seroja Tanjung Jabung Timur Club aged 13 to 15 years is relatively small, amounting to 17 people. Based on the analysis of the passing skills data that has been done, the results obtained are in the good category there are 10 people with a percentage of 59%, for basic dribbling technique skills in the good category there are 12 people with a percentage of 71%, from the basic shooting technique skills test that has been done, the results obtained are in the good category there are 10 people with a percentage of 59%, the overall basic technique skills results from the basic technique skills test of Football in the good category there are 12 people with a percentage of 71%. The conclusion of this study is that the overall basic technique of the basic technique skills test of Football in the good category there are 12 people with a percentage of 71%.